Preparation method and application of photo-thermal response and antibacterial bone filling material
By using a composite material system of Nb2C MXene and CeO2 in orthopedic materials, combined with the binding and functional layers formed by 3D printing technology and bioadhesion characteristics, the problem of existing orthopedic materials lacking photothermal response and antibacterial properties is solved, and the preparation of versatile bone filler materials is achieved, which improves the effect of bone defect repair.
Patent Information
- Application Number
- CN202411921427.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
Existing orthopedic materials lack the versatility of photothermal response and antibacterial properties, making it difficult to achieve effective biocompatibility and mechanical strength in bone defect repair.
Using a composite material system based on Nb2C MXene and CeO2, a porous body is prepared by 3D printing technology, and a binding layer and a functional layer are formed on its surface. The binding layer is formed of tannin and the functional layer is prepared by Nb2C MXene@CeO2.
The material has photothermal response and antibacterial effects under near-infrared light conditions, improves the biological activity and functionality of bone filler materials, and enhances the success rate and safety of bone defect repair.
Smart Images

Figure CN119733102A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical engineering materials, and more specifically relates to a preparation method and application of a bone filling material having both photothermal response and antibacterial properties. Background Art
[0002] With the aggravation of population aging, the incidence of skeletal system diseases such as fractures, osteoporosis, and bone metastases has increased year by year, but the autologous bones and allogeneic bones currently used in clinical practice are limited by insufficient quantity. The medical materials currently used in clinical orthopedics are in great demand, but bioceramics and medical metal materials are limited by their biological inertness and it is difficult to achieve good results. For example, CN202211368220.0 discloses a bone cement composition and a preparation method thereof, in which strontium is cross-linked to calcium sulfate hemihydrate to form a three-dimensional polymer network, but it does not have antibacterial properties. CN202210910869.4 discloses a 3D printed composite bone repair material and its preparation method and application, but the mechanical strength is poor.
[0003] Ideal orthopedic materials should have good biocompatibility and biosafety, and sufficient mechanical strength. What is more needed is that the material should be multifunctional, able to respond to external stimuli, and actively adjust and adapt to the dynamic microenvironment. With its significant advantages in the controllability of scaffold porosity, pore size, pore volume, spatial arrangement and other surface properties, 3D printing technology can design and manufacture personalized bone repair scaffolds according to the specific needs of patients. Photothermal responsive materials are simple and convenient to use, and can achieve local high temperatures under near-infrared light conditions, without relying on the use of antibiotics to destroy bacterial cell walls and intracellular proteins. Although photothermal responsive materials have been used, there are many problems such as single function and high temperature damage to normal tissues, which increases the burden on patients.
[0004] Therefore, how to provide a preparation method and application of a bone filling material that has both photothermal response and antibacterial properties has very important research significance and application value. Summary of the invention
[0005] In view of this, the present invention proposes a composite material system based on Nb2C MXene and CeO2 that has both photothermal response and antibacterial properties. Nb2C MXene has excellent photothermal conversion performance, and its high specific surface area and porosity provide a good drug adsorption and release platform. CeO2 has excellent antibacterial and antioxidant properties. The bonding layer is formed by the bioadhesive properties of tannic acid, connecting the porous body composed of PEI and other engineering plastics through 3D printing and the functional layer composed of MXene@CeO2, which solves many problems in the field of bone defect repair in the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a bone filling material having both photothermal response and antibacterial properties comprises the following steps:
[0008] (1) Preparing a porous main body using medical high-performance engineering plastics: drying the medical high-performance engineering plastics, placing them in a wire drawing machine barrel for heating, and extruding them into filaments to obtain filaments; establishing a pre-printed scaffold structure model according to the shape of the desired bone-filled scaffold, 3D printing the filaments to obtain a porous scaffold, and drying them to obtain a porous main body;
[0009] (2) preparing a binding layer on the surface of the porous body: immersing the porous body in a tannic acid solution, protecting it from light, rinsing it with deionized water, and freeze-drying it for storage;
[0010] (3) Preparation of functional layer using MXene and CeO2: Prepare a solution of Nb2C MXene@CeO2 composite material, put it into the porous body carrying the binding layer for immersion treatment, rinse it with deionized water, and freeze-dry it to obtain a bone filling material.
[0011] Preferably, the specific operations of step (1) include:
[0012] (1.1) Select medical high-performance engineering plastics, place them in an oven at 100-120°C for 12-16 hours to make them fully dry, place them in a wire drawing machine barrel to heat, extrude them into filaments after they are completely melted, and then dry them in an oven at 110-130°C for 2 hours to obtain wire materials;
[0013] (1.2) According to the shape of the required bone-filled scaffold, a pre-printed scaffold structure model is established using 3D modeling software, and converted into an STL file that can be recognized by the 3D printing system; the STL file is imported into the 3D printing system, and the 3D printing nozzle, printing chamber, and molding substrate are preheated by the automatic temperature control system, and then the wire is fed into the preheated 3D printing nozzle by the automatic wire feeding device, and 3D printing is performed according to the trajectory path generated by the software until the printing is completed to obtain a porous scaffold, which is placed in an oven at 100 to 120°C for 10 to 30 minutes for drying to obtain a porous body.
[0014] Preferably, the specific operations of step (2) include:
[0015] The porous body obtained in step (1) is immersed in a tannic acid solution with a pH of 8.5 and a concentration of 2 mg / mL, and is protected from light for 24 to 36 hours at room temperature and in full contact with air. The body is continuously stirred, and is repeatedly rinsed with deionized water for 2 to 3 times to obtain a porous body with a binding layer on the surface, which is freeze-dried for storage.
[0016] Preferably, the specific operations of step (3) include:
[0017] (3.1) Add hydrochloric acid and lithium fluoride to the reaction vessel, stir at room temperature for 30-40 minutes to ensure that lithium fluoride is fully dissolved, continue to add Nb2AlC at 35°C and stir to react, centrifuge at 3500-4000 rpm, discard the supernatant, add water and repeat centrifugation until the solution pH reaches 5, add anhydrous ethanol, and perform 400W ultrasonic treatment for 30-60 minutes under inert gas protection, keeping an ice bath during the period; after ultrasonication, centrifuge at 10000-11000 rpm for 10-15 minutes, collect the precipitate, add deionized water, and pass inert gas again for 400W ultrasonic treatment for 20 minutes, keeping an ice bath during the period; after ultrasonication, centrifuge at 3500-4000 rpm for 3-5 minutes, collect the supernatant, and freeze-dry to obtain Nb2C MXene;
[0018] (3.2) Add Nb2C MXene to deionized water, stir evenly in a nitrogen environment, and perform ultrasonic treatment at 400 W for 30 to 60 min to ensure that Nb2C MXene is evenly dispersed. Continue to add Ce(NO3)3·6H2O, stir to fully mix, drop 0.2M NaOH solution, stir at room temperature for 1 to 1.5 h, react fully, and then perform hydrothermal treatment. Wash the product with ultrapure water, centrifuge at 10000 to 11000 rpm for 10 to 15 min, repeat centrifugation until the pH of the solution reaches 5, and freeze-dry the product for 24 to 72 h to obtain Nb2C MXene@CeO2 composite material;
[0019] (3.3) Adding Nb2C MXene@CeO2 composite material to Tris-HCl buffer to obtain Nb2C MXene@CeO2 solution, then immersing the porous body carrying the binding layer, and placing it on a constant temperature shaker at 37°C for 48 to 72 hours, then taking out the porous body, rinsing it with deionized water, and freeze-drying it to obtain a bone filling material.
[0020] Preferably, the medical high-performance engineering plastic in step (1.1) is selected from one of PEI, PEEK, PEEK doped with 5-10% Si3N4, and PEI doped with 3%-10% β-TCP.
[0021] Preferably, in step (1.1), the wire drawing machine barrel is heated to 320-350° C. and then waited for 3-5 seconds to be completely melted before extrusion;
[0022] The inner diameter of the extrusion port of the wire drawing machine barrel is 1.75±0.10mm.
[0023] The beneficial effect of the above technical solution is that the diameter of the obtained PEI filament can be guaranteed to be within the range of 1.75±0.10 mm.
[0024] Preferably, when 3D printing is performed in step (1.2), the porosity of the porous body is 60% to 70%, and the pore size is 300-700 μm;
[0025] Preheat the 3D printing nozzle to 380-430°C and the molding substrate to 120-150°C.
[0026] Preferably, in step (3.1), the concentration of hydrochloric acid is 9 to 12 M, and Nb2AlC is added and stirred to react for 12 to 36 hours.
[0027] Preferably, in step (3.2), the mass ratio of Nb2C MXene to Ce(NO3)3·6H2O is 2-4:1-3;
[0028] The temperature of the hydrothermal treatment is 120-180°C and the time is 12-24 hours.
[0029] Preferably, in step (3.3), the concentration of Tris-HCl buffer is 10 mmol / L and the pH is 8.5;
[0030] The concentration of Nb2C MXene@CeO2 solution is 1-2 mg / mL.
[0031] The present invention also provides a bone filling material prepared by the above method and having both photothermal response and antibacterial properties, and its application in the field of bone defect repair.
[0032] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides a preparation method and application of a bone filling material having both photothermal response and antibacterial properties, which has the following beneficial effects:
[0033] 1. The present invention can print out a bone-filled scaffold of a desired shape through 3D printing technology, provides reliable parameter support, and ensures personalization and customization; the printed porous body can not only improve the printing efficiency after drying, but also make the different layers of the porous body adhere better, so that the porous body has better integrity and stability.
[0034] 2. The heterojunction of the functional layer not only retains the angiogenesis ability of MXene's own elements, but also obtains the nanozyme-like properties of CeO2. The combination of the two improves the functionality of the material.
[0035] 3. Since the nanoparticles are implanted on the surface of two-dimensional materials with a large specific surface area, they can also work together to achieve an antibacterial effect under the response of near-infrared light. In addition, the nanoparticles are exposed on the surface and can play a role at an early stage.
[0036] 4. The bonding layer can significantly improve the performance of 3D printed bone repair scaffolds. By using the bio-self-adhesive properties of the bonding layer to load the functional layer onto the surface of the porous body, the multifunctional bone filling material formed will significantly enhance the biological activity and functionality of the scaffold, overcoming the limitations of traditional 3D printed scaffolds. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0038] Figure 1 It is a schematic diagram of the structure of the bone filling material of the present invention.
[0039] Figure 2 In the figure, a and b are the SEM and TEM images of Nb2C MXene obtained in Example 1, respectively.
[0040] Figure 3 In the figure, a and b are the SEM and TEM images of the Nb2C MXene@CeO2 composite material obtained in Example 1, respectively.
[0041] Figure 4 To test the antioxidant activity of each product.
[0042] Figure 5 To test the antibacterial rate of each product. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] A multifunctional bone filling material containing Nb2C MXene-CeO2 and a preparation method thereof, comprising the following preparation steps:
[0046] (1) Using medical high-performance engineering plastics to prepare porous bodies:
[0047] (1.1) Select PEI particles, place the PEI particles in an oven at 100°C for 12 hours, place the dried particles in a wire drawing machine barrel, heat the wire drawing machine barrel until the temperature reaches 330°C, wait for 5 seconds, and after the PEI particles are completely melted, extrude (extrusion port inner diameter 1.75±0.1mm) to extrude the PEI into filaments. The extruded PEI filaments are then dried in an oven at 120°C for 2 hours to obtain dry PEI filaments;
[0048] (1.2) According to the shape of the required bone-filled scaffold, a Φ4*5mm scaffold structure model (porosity 60%-70%, pore size 300-700μm) was established using 3D modeling software, and converted into an STL file that can be recognized by the 3D printing system; the STL file was imported into the 3D printing system, the 3D printing nozzle was preheated to 380°C, the molding substrate was preheated to 120°C, and the PEI wire was fed into the preheated printing nozzle through an automatic wire feeding device, and printed layer by layer until the printing was completed to obtain the PEI scaffold, and then the obtained PEI scaffold was dried in a 120°C oven for 30 minutes to obtain a porous body, which was recorded as PEI material;
[0049] (2) Preparing a bonding layer on the surface of the porous body:
[0050] Tannic acid is added to a Tris-HCl buffer solution with a concentration of 10 mmol / L and a pH of 8.5 to prepare a tannic acid solution with a concentration of 2 mg / mL, and the porous body is immersed in the tannic acid solution, and is kept away from light for 24 hours at room temperature and in full contact with air, and is continuously stirred to obtain a porous body with a surface modified by tannic acid, and then the modified porous body is repeatedly rinsed with deionized water for 3 times to obtain a porous body with a binding layer on the surface, and is freeze-dried for storage;
[0051] (3) Use MXene and CeO2 to prepare the functional layer and load it on the surface of the porous body:
[0052] (3.1) Add 2g lithium fluoride (LiF) to 40mL 9M hydrochloric acid in a polytetrafluoroethylene beaker, stir thoroughly at room temperature and 500rpm for 30min to ensure that lithium fluoride is fully dissolved, continue to add 2g Nb2AlC (MAX phase material) in small amounts and multiple times, continue stirring at 35℃ and 500rpm for 12h, centrifuge the mixture at 3500rpm for 10min, discard the supernatant, add 40ml deionized water, continue centrifugation, repeat this process until the solution pH reaches 5, add anhydrous ethanol, pass nitrogen, and perform ultrasonic treatment at 400W for 1h, keeping an ice bath during the period; after the ultrasonic treatment, centrifuge at 10000rpm for 10min, collect the precipitate, add 10mL deionized water, pass nitrogen again, and perform ultrasonic treatment at 400W for 20min, keeping an ice bath during the period; centrifuge at 3500rpm for 3min, collect the supernatant, and freeze-dry the collected supernatant. Obtain Nb2C MXene, such as Figure 1 As shown;
[0053] (3.2) Take 200 mg of Nb2C MXene and add it to 50 mL of deionized water. Stir it evenly at 800 rpm / min in a nitrogen environment, and ultrasonically treat it at 400 W for 30 min to ensure that Nb2C MXene is evenly dispersed. Continue to slowly add 100 mg of cerium nitrate (Ce(NO3)3·6H2O) and stir it to make it fully mixed. Slowly and evenly drip 50 mL of 0.2 M NaOH solution into the mixture, stir it at 500 rpm / min at room temperature for 1 h to fully react, and then transfer it to an autoclave and hydrothermally treat it at 180 °C for 18 h. Wash the product with ultrapure water and centrifuge it at 10000 rpm for 10 min. Repeat the centrifugation until the pH value of the solution reaches 5. The washed product is freeze-dried for 24 h to obtain nanoparticles for preparing the functional layer, namely, Nb2CMXene@CeO2 composite materials, as shown in Figure 2 As shown;
[0054] (3.3) Add Nb2CMXene@CeO2 composite material to 10 mmol / L Tris-HCl buffer with a pH of 8.5 to obtain a Nb2C MXene@CeO2 solution with a concentration of 2 mg / mL; immerse the porous body with a binding layer on the surface in the Nb2C MXene@CeO2 solution, place it on a constant temperature shaker at 37°C for 72 h, take out the porous body, rinse it with deionized water for 3 times, and freeze-dry it to obtain a bone filling material PEI-MXene@CeO2, which is recorded as PMC material.
[0055] Comparative Example 1
[0056] A CeO2 nanoparticle solution was prepared by a hydrothermal method at a concentration of 1 mg / mL. The porous body with a binding layer on the surface obtained in step (2) of Example 1 was immersed in the CeO2 nanoparticle solution and placed on a constant temperature shaker at 37°C for 72 hours. The porous body was then taken out and rinsed with deionized water for three times and freeze-dried to obtain a bone filling material PEI-CeO2, which was recorded as PCe material.
[0057] Comparative Example 2
[0058] The method of step (3.1) of Example 1 was used to prepare a Nb2C MXene solution with a concentration of 2 mg / mL. The porous body with a binding layer on the surface obtained in step (2) of Example 1 was immersed in the Nb2C MXene solution and placed on a constant temperature shaker at 37°C for 72 hours. The porous body was taken out and then rinsed with deionized water for 3 times and freeze-dried to obtain a bone filling material PEI-MXene, which was recorded as PMX material.
[0059] The antibacterial rate test and antioxidant test of each product PEI material, PMC material, PCe material, and PMX material were carried out. The results are as follows Figure 4 and Figure 5 shown.
[0060] Antibacterial rate experiment: Staphylococcus aureus and Escherichia coli were co-cultured with each product for 3 h and then subjected to photothermal treatment. After culturing at 37 °C for 20 h, the antibacterial rate was verified by the plate coating method;
[0061] Antioxidant activity experiment: CCK-8 method was used to detect the cell activity after H2O2 treatment.
[0062] According to experiments, the technical solution of Example 1 has at least the following technical effects or advantages:
[0063] Nb2C MXene has good biocompatibility, and its high porosity and high specific surface area can provide good nanoparticle loading sites. The added CeO2 has excellent antioxidant properties, which can remove reactive oxygen species (ROS) in the body and reduce postoperative inflammatory reactions, such as Figure 4 As shown. Nb2CMXene@CeO2 composite materials can also generate local high temperatures under near-infrared light irradiation and have significant antibacterial effects, such as Figure 5 As shown, the success rate and safety of bone repair can be further improved.
[0064] Example 2
[0065] The difference between Example 2 and Example 1 is that: in step (1), the medical high-performance engineering plastic is PEEK mixed with 10% Si3N4, the 3D printing nozzle is preheated to 430°C, and the molding substrate is preheated to 150°C; in step (3), the temperature of the hydrothermal treatment is 160°C and the time is 24h. The rest is the same.
[0066] The technical solution of Example 2 has at least the following technical effects or advantages:
[0067] Adding Si3N4 to PEEK can improve the thermal conductivity of the porous scaffold body and its response to near-infrared light. On the one hand, it can transfer heat energy to the tissue more evenly and quickly, improving the antibacterial therapeutic effect of near-infrared light. On the other hand, at mild temperatures, it can improve local blood circulation, promote the proliferation and differentiation of bone cells, and thus accelerate the integration process of bone tissue and scaffold.
[0068] During hydrothermal treatment, lowering the reaction temperature and increasing the hydrothermal time can make the reaction more complete and increase the yield, while also improving the efficiency of the functional layer to a certain extent. Lowering the reaction temperature can reduce the occurrence of side reactions, avoid material decomposition or structural damage caused by high temperature, and form a tighter load layer. The optimized physical structure and chemical stability enable the functional layer to provide more lasting support and more effective effects during bone repair.
[0069] Example 3
[0070] The difference between Example 3 and Example 1 is that: in step (1), the medical high-performance engineering plastic is PEI mixed with 5% β-TCP, the 3D printing nozzle is preheated to 390°C, and the molding substrate is preheated to 150°C; in step (3.1), 2g of lithium fluoride (LiF) is added to 40mL of 12M hydrochloric acid in a polytetrafluoroethylene beaker, and the mixture is stirred at room temperature and 500rpm for 30min to ensure that the lithium fluoride is fully dissolved, and 2g of Nb2AlC (MAX phase material) is added in small amounts and multiple times, and the mixture is stirred at 25°C and 500rpm for 24h. The rest is the same.
[0071] The technical solution of Example 3 has at least the following technical effects or advantages:
[0072] Increasing the concentration of hydrochloric acid and extending the reaction time can effectively improve the reaction efficiency, ensure that the material reacts fully, and reduce the amount of material loss during the reaction. This adjustment not only helps to improve the purity and yield of the final product, but also further enhances the physical and chemical properties of the material, providing a more reliable guarantee for subsequent applications.
[0073] Increasing the temperature of the print head allows the material to flow more easily during the printing process, reducing the possibility of blockage and printing interruption. The smooth filament discharge process significantly improves printing efficiency, shortens production time, and can quickly complete the printing of complex structures. PEI incorporated with β-TCP not only provides the key minerals required for osteogenesis, but also enhances the porosity and surface roughness of the scaffold, thereby accelerating the repair process of the bone defect area. This material combination also improves the compressive strength and flexural strength of the scaffold, making its mechanical properties closer to natural bone, thereby providing effective mechanical support for the bone defect area.
[0074] Application Examples
[0075] The multifunctional bone filling scaffold material of the present invention is particularly suitable for treating bone defects caused by diseases, accidents or surgeries. For example, after fracture repair or bone tumor resection, patients may face bone defects. At this time, the material of the present invention can be used as an ideal filler to promote bone tissue regeneration and healing.
[0076] The bone filling material obtained in Example 1 was implanted in the form of a screw into the tibial defect of a rabbit with anterior cruciate ligament injury. Due to its excellent bioadhesion and biocompatibility, it can quickly combine with the surrounding bone tissue and reduce the risk of infection through the photothermal conversion ability of the bonding layer. In addition, due to the porous structure design of the scaffold material, it provides a good growth space for cells, which is conducive to the migration and proliferation of cells and further promotes the formation of bone tissue. The application of this scaffold material effectively improves the success rate of bone defect repair.
[0077] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a bone filling material having both photothermal response and antibacterial properties, characterized in that: The following steps are involved: (1) Preparing a porous main body using medical high-performance engineering plastics: drying the medical high-performance engineering plastics, placing them in a wire drawing machine barrel for heating, and extruding them into filaments to obtain filaments; establishing a pre-printed scaffold structure model according to the shape of the desired bone-filled scaffold, 3D printing the filaments to obtain a porous scaffold, and drying them to obtain a porous main body; (2) preparing a binding layer on the surface of the porous body: immersing the porous body in a tannic acid solution, protecting it from light, rinsing it with deionized water, and freeze-drying it for storage; (3) Preparation of functional layer using MXene and CeO2: Prepare a solution of Nb2C MXene@CeO2 composite material, put it into the porous body carrying the binding layer for immersion treatment, rinse it with deionized water, and freeze-dry it to obtain a bone filling material.
2. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 1, characterized in that: The specific operations of step (1) include: (1.1) Select medical high-performance engineering plastics, place them in an oven at 100-120°C for 12-16 hours to make them fully dry, place them in a wire drawing machine barrel to heat, extrude them into filaments after they are completely melted, and then dry them in an oven at 110-130°C for 2 hours to obtain wire materials; (1.2) According to the shape of the required bone-filled scaffold, a pre-printed scaffold structure model is established using 3D modeling software, and converted into an STL file that can be recognized by the 3D printing system; the STL file is imported into the 3D printing system, and the 3D printing nozzle, printing chamber, and molding substrate are preheated by the automatic temperature control system, and then the wire is fed into the preheated 3D printing nozzle by the automatic wire feeding device, and 3D printing is performed according to the trajectory path generated by the software until the printing is completed to obtain a porous scaffold, which is placed in an oven at 100 to 120°C for 10 to 30 minutes for drying to obtain a porous body.
3. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 1, characterized in that: The specific operations of step (3) include: (3.1) Add hydrochloric acid and lithium fluoride to the reaction vessel, stir at room temperature to ensure that lithium fluoride is fully dissolved, continue to add Nb2AlC and stir to react, centrifuge, discard the supernatant, add water and repeat centrifugation until the solution pH reaches 5, add anhydrous ethanol, and perform ultrasonic treatment under the protection of inert gas, keeping an ice bath during the period; after ultrasonication, centrifuge, collect the precipitate, add deionized water, and pass inert gas again for ultrasonic treatment, keeping an ice bath during the period; after ultrasonication, centrifuge, collect the supernatant, and freeze-dry to obtain Nb2C MXene; (3.2) Add Nb2C MXene to deionized water, stir evenly in a nitrogen environment, and perform ultrasonic treatment to ensure that Nb2C MXene is evenly dispersed. Continue to add Ce(NO3)3·6H2O, stir to fully mix, drop into 0.2M NaOH solution, stir at room temperature, react fully, and then perform hydrothermal treatment. Wash the product with ultrapure water, repeat centrifugation until the pH of the solution reaches 5, and freeze-dry the product to obtain a Nb2C MXene@CeO2 composite material. (3.3) Adding Nb2C MXene@CeO2 composite material to Tris-HCl buffer to obtain Nb2C MXene@CeO2 solution, then immersing the porous body carrying the binding layer and placing it on a constant temperature shaker for treatment, then taking out the porous body, rinsing it with deionized water, and freeze-drying it to obtain a bone filling material.
4. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 2, characterized in that: The medical high-performance engineering plastic in step (1.1) is selected from one of PEI, PEEK, PEEK mixed with 5-10% Si3N4, and PEI mixed with 3%-10% β-TCP.
5. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 2, characterized in that: In step (1.1), the wire drawing machine barrel is heated to 320-350°C and then waited for 3-5 seconds to be completely melted before extrusion; The inner diameter of the extrusion port of the wire drawing machine barrel is 1.75±0.10mm.
6. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 2, characterized in that: When 3D printing is performed in step (1.2), the porosity of the porous body is 60% to 70%, and the pore size is 300-700 μm; Preheat the 3D printing nozzle to 380-430°C and the molding substrate to 120-150°C.
7. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 3, characterized in that: In step (3.1), the concentration of hydrochloric acid is 9 to 12 M, and Nb2AlC is added and stirred to react for 12 to 36 hours.
8. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 3, characterized in that: In step (3.2), the mass ratio of Nb2C MXene and Ce(NO3)3·6H2O is 2-4:1-3; The temperature of the hydrothermal treatment is 120-180°C and the time is 12-24 hours.
9. The method for preparing a bone filling material having both photothermal response and antibacterial properties according to claim 3, characterized in that: In step (3.3), the concentration of Tris-HCl buffer is 10 mmol / L and the pH is 8.5; The concentration of Nb2C MXene@CeO2 solution is 1-2 mg / mL.
10. Use of a bone filling material having both photothermal response and antibacterial properties prepared by the method according to any one of claims 1 to 9 in the field of bone defect repair.
Citation Information
Patent Citations
A 3D-printed composite bone repair material, its preparation method and application
CN115177787B
Bone cement composition and preparation method thereof
CN115645622A